Schistosomiasis prevalence and low-cost diagnostics in rural Northwestern Madagascar: a pilot study - Kyle E. Robinson; Eric P. Grewal; Bobbi S. Pritt; Margaret Lloyd; Adriantiano M. Stephano; Mamantsara Fardine; Lisa M. Brumble; Claudia R. Libertin (Journal of Global Health Reports)
# Background Schistosomiasis is a parasitic disease that affects the health of hundreds of millions of people worldwide. Affordable diagnostic methods are necessary for developing countries to monitor schistosomiasis rates and treat infected individuals, particularly in, Madagascar, a country with the world’s fifth highest rate of schistosomiasis.